LECT2 promotes inflammation and insulin resistance in adipocytes via P38 pathways. (July 2018) - Jung, Tae Woo; Chung, Yoon Hee; Kim, Hyoung-Chun; Abd El-Aty, A M; Jeong, Ji Hoon
Abstract : Leukocyte cell-derived chemotaxin 2 (LECT2) is a recently identified novel hepatokine that causes insulin resistance in skeletal muscle by activating c-Jun N-terminal kinase (JNK), thereby driving atherosclerotic inflammation. However, the role of LECT2 in inflammation and insulin resistance in adipocytes has not been investigated. In this study, we report that LECT2 treatment of differentiated 3T3-L1 cells stimulates P38 phosphorylation in a dose-dependent manner. LECT2 also enhanced inflammation markers such as IκB phosphorylation, nuclear factor kappa beta (NF-κB) phosphorylation and IL-6 expression. Moreover, LECT2 treatment impaired insulin signaling in differentiated 3T3-L1 cells, as evidenced by the decreased levels of insulin receptor substrate (IRS-1) and Akt phosphorylation and reduced insulin-stimulated glucose uptake. Furthermore, LECT2 augmented lipid accumulation during 3T3-L1 cell differentiation by activating SREBP1c-mediated signaling. All these effects were significantly abrogated by siRNA-mediated silencing of P38, CD209 expression or a JNK inhibitor. Our findings suggest that LECT2 stimulates inflammation and insulin resistance in adipocytes via activation of a CD209/P38-dependent pathway. Thus, these results suggest effective therapeutic targets for treating inflammation-mediated insulin resistance.